INTEGRATION OF ENVIRONMENTAL FACTORS AND ECONOMIC COMPONENTS - THE RESOURCE BASE OF ECONOMIC GROWTH - Журавська, Наталія; Неудачина, А. (SWorldJournal, 2024)
Facilitating the formation of the foundations of an ecological and economic worldview, taking into account the economic aspects of nature management and environmental protection legislation, is a necessary component that allows future specialists to deter